Mutations at Residues 282, 286, and 293 of Phage λ Integrase Exert Pathway-Specific Effects on Synapsis and Catalysis in Recombination - Bankhead, Troy M. (American Society for Microbiology, 2003)
Bacteriophage λ integrase (Int) catalyzes site-specific recombination between pairs of attachment (att) sites. The att sites contain weak Int-binding sites called core-type sites that are separated by a 7-bp overlap region, where cleavage and strand exchange occur. We have characterized a number of mutant Int proteins with substitutions at positions S282 (S282A, S282F, and S282T), S286 (S286A, S286L, and S286T), and R293 (R293E, R293K, and R293Q). We investigated the core- and arm-binding properties and cooperativity of the mutant proteins, their ability to catalyze cleavage, and their ability to form and resolve Holliday junctions. Our kinetic analyses have identified synapsis as the rate-limiting step in excisive recombination. The IntS282 and IntS286 mutants show defects in synapsis in the bent-L and excisive pathways, respectively, while the IntR293 mutants exhibit synapsis defects in both the excision and bent-L pathways. The results of our study support earlier findings that the catalytic domain also serves a role in binding to core-type sites, that the core contacts made by this domain are important for both synapsis and catalysis, and that Int contacts core-type sites differently among the four recombination pathways. We speculate that these residues are important for the proper positioning of the catalytic residues involved in the recombination reaction and that their positions differ in the distinct nucleoprotein architectures formed during each pathway. Finally, we found that not all catalytic events in excision follow synapsis: the attL site probably undergoes several rounds of cleavage and ligation before it synapses and exchanges DNA with attR.